Analysis of the Relationship between Digital-Based Work-Life Integration and Generation Z Employee Loyalty in the Creative Business Sector - Kapsah, Kapsah; Aprili, Ronaldo (Universitas Sains dan Teknologi Komputer, 2024)
Digital transformation in the creative business sector has reshaped work patterns among employees, particularly Generation Z, leading to a shift from the concept of work-life balance toward digital-based work-life integration. This study aims to examine the relationship between digital-based work-life integration and employee loyalty among Generation Z workers in Indonesia’s creative industry. A mixed methods sequential explanatory design was employed, combining an online survey of 150 Generation Z employees with in-depth interviews involving 10 key informants to obtain both quantitative evidence and qualitative insights. The findings indicate that the integration of work and personal life supported by flexible working time, location, and adaptive boundary management is positively associated with affective commitment, intention to stay, and willingness to contribute to the organization. Qualitative results further reveal that unmanaged digital connectivity may lead to digital fatigue, which in certain conditions weakens employee loyalty. This study contributes theoretically by extending the work-life integration framework through the inclusion of employee loyalty as a key outcome, and practically by offering guidance for creative organizations in designing balanced digital work policies to enhance retention and engagement among Generation Z employees.